A New Motif in the N‐Terminal of Acetylcholinesterase Triggers Amyloid‐β Aggregation and Deposition - Hou, Li‐Na (CNS Neurosci Ther, 2013)
BACKGROUND AND PURPOSE: As a molecular chaperone, acetylcholinesterase (AChE; EC 3.1.1.7) plays a critical role in the pathogenesis of Alzheimer's disease (AD). The peripheral anionic site (PAS) of AChE has been indicated as the amyloid‐β (Aβ) binding domain. The goal of this study was to determine other motifs in AChE involved in Aβ aggregation and deposition. METHODS AND RESULTS: The β‐hairpin in monomeric Aβ is the key motif of nucleation‐dependent Aβ self‐aggregation. As AChE could induce Aβ aggregation and deposition, we searched AChE for β‐hairpin structures. In A11‐specific dot blot assay, AChE was detected by an oligomer‐specific antibody A11, implying the existence of β‐hairpin structures in AChE as β‐hairpin was the core motif of oligomers. A molecular superimposing approach further revealed that the N‐terminal region, from Glu7 to Ile20, in AChE (AChE 7–20) was similar to the β‐hairpin domain in Aβ. The results of further dot blot assays, thioflavin T fluorescence assays, and electron microscopy imaging experiments, indicated that the N‐terminal synthetic peptide AChE (7–20) had nearly the same ability as AChE with regard to triggering Aβ aggregation and deposition. CONCLUSIONS: AChE 7–20, a β‐hairpin region in AChE, might be a new motif in AChE capable of triggering Aβ aggregation and deposition. This finding will be helpful to design new and more effective Aβ aggregation inhibitors for AD treatment.